2007
DOI: 10.1016/j.ica.2006.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and calculated circular dichroism spectra of monoaza[5]helicenes

Abstract: Circular dichroism (CD) spectra have been measured in the range of 400-200 nm on CH 3 OH solutions of both enantiomers for the almost complete series of monoaza [5]helicenes, namely the molecules where the hetero N atom occupies positions 1, 3, 4, 5, 6, and 7, respectively (the 2 isomer is missing due to difficulties in the synthesis). CD spectra recorded at controlled room temperature allow one to define precise racemization rates, that are nicely interpreted on the basis of DFT molecular orbital calculations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…Surprisingly,t he experimental data show the opposite (vide infra). These calculations concerning compounds 1, 2,a nd 8 corroborate the findings recently published in an extensive study on pyrido [5]-and pyrido [6]helicene by Stary et al [19] In particular,t he calculated activation barriers DG ¼ 6 298 K agree very well with the remarkablyl ow barrier calculated for compound 1 and geometrical parameters are comparable, including the intramolecular improper blue-shifting hydrogen bond established in the TS of compound 1. [16,20,21] Some key structural parameters of the transition-state structures obtained by DFT calculations at the B3LYP/6-311G(d,p) level, describing the distortion of the fused rings system from planarity,a re summarized in Ta ble 2.…”
Section: Quantumc Hemical Calculations(dft)supporting
confidence: 86%
See 2 more Smart Citations
“…Surprisingly,t he experimental data show the opposite (vide infra). These calculations concerning compounds 1, 2,a nd 8 corroborate the findings recently published in an extensive study on pyrido [5]-and pyrido [6]helicene by Stary et al [19] In particular,t he calculated activation barriers DG ¼ 6 298 K agree very well with the remarkablyl ow barrier calculated for compound 1 and geometrical parameters are comparable, including the intramolecular improper blue-shifting hydrogen bond established in the TS of compound 1. [16,20,21] Some key structural parameters of the transition-state structures obtained by DFT calculations at the B3LYP/6-311G(d,p) level, describing the distortion of the fused rings system from planarity,a re summarized in Ta ble 2.…”
Section: Quantumc Hemical Calculations(dft)supporting
confidence: 86%
“…As am odel for understanding the unexpected differenceb etween experimental DHPLC and calculated values in the gas phase for compound 1 (see Ta ble 1), the influence of the presence of an explicit solvent molecule [22] wasi nvestigated. Hydrogen bonding and protonation were also considered in related studies to explain the dimerization and proton affinities of 1-aza [6]helicene and 2-aza [6]helicene determined by mass spectrometry. [23,24] The formation of ac omplex between 1 in its minimum-energy conformation GS ando ne 2-propanol molecule via an OH···N hydrogen bond ( Figure 3) was simulated, resultingi na nO ( ÀH)···N distance of 2.95 ( shortert han the sum of Oa nd Nv an der Waals radii)a nd an OÀH···N angle of about 1508.B 3LYP/ 6-311G(d,p) and wB97X-D/6-311G(d,p) calculations estimate intermoleculari nteraction energies of 28.5 and 29.0 kJ mol À1 ,r espectively,t hus explaining the gap between the calculated and experimental energy barrier for compound 1.I nf act, the formation of TS implies the disruption of this hydrogen bond because the nonbonding pair of the Na tom oc- Chem.E ur.J.2015, 21,13919 -13924 www.chemeurj.org cupies as p 2 -hybridized orbital strongly coordinated with the HÀC (14) moiety.T he nonbonding Np air becomes ap oor hydrogen bond acceptor and it is no longera ble to coordinate with isopropanol molecules thus accounting for the energy differencec orresponding to the breakage of this hydrogen bond.…”
Section: Quantumc Hemical Calculations(dft)mentioning
confidence: 99%
See 1 more Smart Citation
“…The half-life times were completed in 2007 for the all series of aza [5]helicenes. 85 Scheme 9. Synthesis of mono-and bis-aza- [5]helicenes investigated by oxidative photocyclization, except 35b 2 which was prepared by an acid cyclization process.…”
Section: Oxidative Photocyclizationmentioning
confidence: 99%
“…Although an increase in the number of ortho annulated rings generally leads to an increase in the racemization time and conformational stability, some tetracyclic compounds exhibit an unusually high thermal conformational stability. 52,[55][56][57] A comprehensive study of the circular dichroism properties of monoaza[5]helicenes was conducted by Caronna et al 61,62 It was observed that although the studied compounds showed similar features to the parent [5]helicene, all of them had shorter racemization time and showed distinct features due to the presence of the nitrogen atom. Ihmels and coworkers 63 showed that diazonia derivatives 46, 47 and 48 have a high binding selectivity for triple-helical DNA, most probably due to their double charge and helical molecular shape.…”
Section: Propertiesmentioning
confidence: 99%